Method statement for reinforced concrete frame structure of residential building - Mohd Shah, Muhammad Aiman Zihni (Universiti Teknologi MARA, Perak, 2019)
One of the most commonly used contemporary construction products is reinforced concrete. By blending cement, sand, and aggregates with waler, concrete is "artificial rock." Fresh concrete can be molded into almost any shape, which is an inherent advantage over other materials. Concrete became very common following the 19th century creation of Portland cement; its restricted resistance to stress, however, avoided its broad use in construction. Steel bars are integrated in concrete to resolve this deficiency in order to create a composite material called strengthened concrete. In the early 19th century, European technicians developed developments in contemporary reinforced concrete design and building exercise. Reinforced concrete is currently being used widely in a broad range of engineering applications.